IMPORTANT PEDAGOGICAL ASPECTS OF TRAINING FUTURE MILITARY PERSONNEL - Djumaeva Sanobar Absaatovna; Kholdorov Nurlan Makhamatkul ugli (Academia Science Repository, 2023)
Personnel training institutions are the stage that determines the level of the working class of the entire society. This article discusses the current state of military educational institutions and reforms to be implemented based on the current problems of training future military personnel.